Synthesis and bioactivities evaluation of oleanolic acid oxime ester derivatives as α-glucosidase and α-amylase inhibitors - Xu-Yang Deng; Jun-Jie Ke; Ying-Ying Zheng; Dong-Li Li; Kun Zhang; Xi Zheng; Jing-Ying Wu; Zhuang Xiong; Pan-Pan Wu; Xue-Tao Xu (Taylor & Francis Group, 2022)
Different oleanolic acid (OA) oxime ester derivatives (3a-3t) were designed and synthesised to develop inhibitors against α-glucosidase and α-amylase. All the synthesised OA derivatives were evaluated against α-glucosidase and α-amylase in vitro. Among them, compound 3a showed the highest α-glucosidase inhibition with an IC50 of 0.35 µM, which was ∼1900 times stronger than that of acarbose, meanwhile compound 3f exhibited the highest α-amylase inhibitory with an IC50 of 3.80 µM that was ∼26 times higher than that of acarbose. The inhibition kinetic studies showed that the inhibitory mechanism of compounds 3a and 3f were reversible and mixed types towards α-glucosidase and α-amylase, respectively. Molecular docking studies analysed the interaction between compound and two enzymes, respectively. Furthermore, cytotoxicity evaluation assay demonstrated a high level of safety profile of compounds 3a and 3f against 3T3-L1 and HepG2 cells.Highlights Oleanolic acid oxime ester derivatives (3a-3t) were synthesised and screened against α-glucosidase and α-amylase. Compound 3a showed the highest α-glucosidase inhibitory with IC50 of 0.35 µM. Compound 3f presented the highest α-amylase inhibitory with IC50 of 3.80 µM. Kinetic studies and in silico studies analysed the binding between compounds and α-glucosidase or α-amylase.